Identifikasi Spesies Reaktif yang Dihasilkan Plasma Nonthermal lucutan penghalang dielektrik permukaan dengan Variasi Sumber Gas (Udara, N2, O2) untuk Membunuh Bakteri - Renaldo Apriandi Kasa; Unggul Pundjung Juswono; Dionysius Joseph Djoko Herry Santjojo (Postgraduate, University of Mataram, 2022)
Non-thermal plasma is one of the new techniques that is being focused on in the medical world, one of which is used for sterilization because non-thermal plasma is known to have a bactericidal effect. Reactive species produced by non-thermal plasma are antimicrobial. One factor affecting plasma species' reactive composition is the gas source used. Therefore, this study aimed to determine the effect of reactive species produced from non-thermal plasma generation of SDBD using different gas sources, namely free air, oxygen, and nitrogen, in treating Escherichia Coli bacteria. The gas flow used is 1 liter/minute. Reactive species produced by plasma were characterized using Optical Emission Spectrometry (OES). SDBD Non-thermal plasma treatment for Escherichia Coli bacteria samples was repeated three times for each treatment, and then the Anova test was performed. The results of this study indicate that bacterial death at the decontamination level depends on the composition of the gas used during treatment. Plasma using an O2 gas source has a more effective inactivation ability, namely 6 x 107 CFU/ml, compared to the control, which is 409 x 107 CFU/ml. At the same time, the treatment results with free air and nitrogen gas sources were 6.33 x 107 CFU/ml and 41.67 x 107 CFU/ml. These results indicate that the composition of ROS and RNS influences bacterial inactivation, where ROS is more effective in inactivating bacteria than RNS